Empowering our people: Predictors of retention in an STI risk reduction program among rural Native Americans with binge substance use. Issue 2 (24th May 2021) - Tingey, Lauren; Rosenstock, Summer; Chambers, Rachel; Patel, Hima; Melgar, Laura; Slimp, Anna; Lee, Angelita; Cwik, Mary; Rompalo, Anne; Gaydos, Charlotte
Abstract: Purpose: Substance use and sexual risk‐taking have been shown to co‐occur. Programs focused on sexually transmitted infections (STIs) reduction may benefit substance‐using, particularly binge substance‐using, adults. This is especially true for rural Native American communities who endure sexual and substance use disparities and have few STI risk reduction programs. This study explores factors predicting retention in an STI risk reduction program among rural Native adults engaged in binge substance use. Methods: We analyzed data from 150 Native adults ages 18‐55 participating in an evaluation of "EMPWR, " a 2‐session STI risk reduction program in a rural, reservation‐based community. Multivariate logistic regression models were used to estimate associations between independent variables and program completion across demographics, sexual behaviors, substance use behaviors, mental health, recent health care utilization, and perceived enculturation and discrimination. Findings: The sample was 49.2% (n = 59) female with a mean age of 33.61 years (SD = 8.25). Twenty‐six completed only the first EMPWR session, 94 completed both EMPWR sessions, and 30 were randomized but completed 0 sessions. Being married/cohabiting (adjusted odds ratio [AOR] = 6.40, P = .0063) and living with an older generation (AOR = 4.86, P = .0058) were significantly associated with higher odds of completing EMPWR. Conclusions: Findings provide insight on factors driving retention of Natives with recent binge substance use in STI risk reduction programming. An important contribution to Native health literature is that living with an older generation positively predicted EMPWR program completion, suggesting that STI risk reduction programs should harness the strength of families to ensure program attendance and optimize impacts in rural reservation contexts.